CD4+ T Follicular Helper and IgA+ B Cell Numbers in Gut Biopsies from HIV-Infected Subjects on Antiretroviral Therapy Are Similar to HIV-Uninfected Individuals - Zaunders, John; Danta, Mark; Bailey, Michelle; Mak, Gerald; Marks, Katherine; Seddiki, Nabila; Xu, Yin; Templeton, David J.; Cooper, David A.; Boyd, Mark A.; Kelleher, Anthony D.; Koelsch, Kersten K. (Frontiers in Immunology, 2016)
Background: Disruption of gastrointestinal tract epithelial and immune barriers contribute to microbial translocation, systemic inflammation and progression of HIV-1 infection. Antiretroviral therapy (ART) may lead to reconstitution of CD4+ T cells in gastrointestinal-associated lymphoid tissue (GALT), but its impact on humoral immunity within GALT is unclear. Therefore we studied CD4+ subsets, including T follicular helper cells (Tfh), as well as resident B cells that have switched to IgA production, in gut biopsies, from HIV+ subjects on suppressive ART, compared to HIV-negative controls. Methods: 23 HIV+ subjects on ART and 22 HIV-negative controls (HNC) undergoing colonoscopy were recruited to the study. Single cell suspensions were prepared from biopsies from left colon (LC), right colon (RC) and terminal ileum (TI). T and B lymphocyte subsets, as well as EpCAM+ epithelial cells, were accurately enumerated by flow cytometry, using counting beads. Results: No significant differences in the number of recovered epithelial cells were observed between the two subject groups. However, the median TI CD4+ T cell count/106 epithelial cells was 2.4-fold lower in HIV+ subjects versus HNC (19,679 vs 47,504 cells; p=0.02). Similarly, median LC CD4+ T cell counts were reduced in HIV+ subjects (8,358 vs 18,577; p=0.03), but were not reduced in RC. Importantly, we found no significant differences in Tfh or IgA+ B cell counts at either site between HIV+ subjects and HNC. Further analysis showed no difference in CD4+, Tfh or IgA+ B cell counts between subjects who commenced ART in primary compared to chronic HIV-1 infection. Despite the decrease in total CD4 T cells, we could not identify a selective decrease of other key subsets of CD4+ T cells, including: CCR5+ cells; CD127+ long-term memory cells; CD103+ tissue resident cells; or CD161+ cells (surrogate marker for Th17), but there was a slight increase in the proportion of T regulatory cells. Conclusion: While there were lower absolute CD4+ counts in the TI and LC in HIV+ subjects on ART, they were not associated with significantly reduced Tfh cell counts or IgA+ B cells, suggesting that this important vanguard of adaptive immune defense against luminal microbial products is normalised following ART.